Implementasi barcode tree sebagai sarana penunjang literasi siswa (studi kasus di man 1 kota probolinggo) - Rokhmah, Ica Khadiqotur (Maliki Interdisciplinary Journal, 2025)
Literacy is one of the crucial components of education. With literacy, students will find it easier to receive and absorb information. MAN 1 Kota Probolinggo implemented a digital literacy platform called “Barcode Tree.” So, this research was conducted to examine the application of Barcode Tree further to increase the reading interest of MAN 1 Kota Probolinggo students. The method used is descriptive qualitative with case study analysis. Thus, the author examines the application of the Barcode Tree and presents the data through descriptive analysis exposure. Digital literacy is one of the means that is quite calculated. Thus, the application of the Barcode Tree is enough to provide significant results in improving the literacy of MAN 1 Kota Probolinggo students.